PEMBERDAYAAN PEREMPUAN MELALUI PEMAHAMAN METODE KONTRASEPSI DALAM MENINGKATKAN KUALITAS HIDUP KELUARGA DI DESA TELLUMPOCCOE KEC. MARUSU KAB. MAROS - Hamang, Sitti Hadriyanti; Masnilawati, Andi; Nia Karuniawati; Nurhayati Nurhayati (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2022)
The importance of using family planning contraceptives is that government programs aim to control population growth, limit birth rates and regulate birth spacing so as to create healthy and prosperous families. This program is also expected to reduce maternal and infant mortality due to unwanted pregnancies or birth spacing that is too close. Efforts to support the program are using contraceptives to delay pregnancy and space or space births. One of the main points in the National Family Planning program is to gather and invite all community potentials to actively participate in institutionalizing and cultivating the Small Happy and Prosperous Family Norm in order to improve the quality of Indonesian human resources. The method used to realize the Small Happy and Prosperous Family Norm is to regulate the spacing of children's births by using a contraceptive device (Wiknjosastro, 2005). Long-term contraceptive method (MKJP) has proven to be the most effective in reducing pregnancy rates. However, until now MKJP is still not the choice of the majority of couples of childbearing age in Indonesia. Types of MKJP such as IUDs, IUDs, and sterilization in the form of vasectomy and tubectomy have been scientifically proven to be the most effective methods of spacing pregnancies. However, MKJP users in Indonesia are still very low. The purpose of this service is to disseminate and provide family planning counseling by empowering women about long-term contraceptive methods and non-long-term contraceptive methods where this is in line with government programs, namely the recommendation to use these methods.